2015
DOI: 10.1016/j.toxrep.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared (FT-IR) study on cyanide induced biochemical and structural changes in rat sperm

Abstract: HighlightsLower doses of cyanide did not alter the biochemical compositions in rat sperms.Higher doses of cyanide had induced significant decrease in biochemical compositions in rat sperms.Cyanide induced alterations in secondary structure of proteins present in rat sperms.FT-IR spectroscopy is a powerful tool used to investigate oxidative damage in sperms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
(77 reference statements)
3
16
0
Order By: Relevance
“…We also observed vacuolar degeneration of Sertoli and spermatogenic cells and necrosis of Leydig cells showing deep eosinophilic cytoplasmic staining. This is similar to the results of the study of Shivanoor and David, who showed that exposure to cyanide caused oxidative damage in sperm biomolecules and reproductive organs, resulting in altered sperm function and toxicity to male genital and reproductive organs (Shivanoor & David, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…We also observed vacuolar degeneration of Sertoli and spermatogenic cells and necrosis of Leydig cells showing deep eosinophilic cytoplasmic staining. This is similar to the results of the study of Shivanoor and David, who showed that exposure to cyanide caused oxidative damage in sperm biomolecules and reproductive organs, resulting in altered sperm function and toxicity to male genital and reproductive organs (Shivanoor & David, 2015).…”
Section: Discussionsupporting
confidence: 91%
“… 72 , Raskó and Kiss 71 2269 N=C=O groups (isocyanate) 2272 –O–C≡N groups 3 Júnior et al 73 2199 C≡N stretching (nitrile group) 72 Ruhland et al 74 2144 C–H stretching in alkanes or alkyne C≡C triple bond stretch 128 Coelho et al 75 ; Zhang et al 76 ; Mamunya and Iurzhenko 77 1648 C=O, C=C stretching 1646 C=O, C=C stretching (amide-I, protein C=O stretching) 2 Shashoua et al . 78 , Sławomir 79 1544 C=C stretching or Amide–II (protein N–H bend, C–N stretch) Ivanova and Kolev 81 , Mallappa and Muniswamy 82 1441 CH 2 –bending vibrations of the methyl group; lipids and proteins) 1436 O–CH 3 methyl esters –5 Drasar and Khripach 83 ; Singh et al 57 1277 C–O stretching 1256 PO asymmetric vibrations (phosphate I) –21 Ashtarinezhad et al . 84 , Sławomir 79 1053 PO 4 group vibration …”
Section: Resultsmentioning
confidence: 99%
“…The FTIR peaks located at 1640 and 1540 cm −1 indicate the presence of proteins 80 . In addition to these peaks, one peak at 1544 cm −1 in the spectral range may be attributed to stretching vibration of carboxyl (–CO), C=C stretching or amide-II (C–N stretch, protein N–H bend) groups 23 , 81 , 82 , this peak disappeared in the FTIR spectrum of the Gracilaria biomass sample after biosorption process. The peaks at 1530–1560 cm –1 are attributed to stretching vibration of amino groups (NH stretching) 67 .…”
Section: Resultsmentioning
confidence: 99%
“…Cyanide is a potent Complex IV or CIV inhibitor that results in cellular bioenergetic failure from decreased ATP production [ [1] , [2] , [3] , [4] ]. Cyanide exposure can occur from smoke inhalation, especially following the combustion of materials that include wool, silk, synthetic rubber, and polyurethane.…”
Section: Introductionmentioning
confidence: 99%